Speciation of Genes and Genomes: Conservation of DNA Polymorphism by Barriers to Recombination Raised by Mismatch Repair System - Radman, Miroslav (Frontiers in Genetics, 2022)
Some basic aspects of human and animal biology and evolution involve the establishment of biological uniqueness of species and individuals within their large variety. The discrimination of closely related species occurs in their offspring at the level of chromosomal DNA sequence homology required for fertility, which is the hallmark of species. Biological identification of individuals, i.e., of their biological “self”, occurs at the level of protein sequences presented by the MHC/HLA complex as part of the immune system which discriminates non-self from self. Here, I present a mechanistic molecular model that can explain how DNA sequence divergence and the activity of key mismatch repair proteins MutS and MutL lead to: (i)(Queiroz, 2005) genetic separation of closely related species (sympatric speciation) and (ii) conservation of polymorphic DNA sequence blocks that constitute the immunological self. DNA sequence divergence leads to formation of mismatched base pairs in hybrid DNA created by strand exchange during homologous recombination. Detection of such base-pair mismatches by mismatch repair proteins leads to avoidance and even reversal of initiated recombination events. Precluding recombination by the polymorphism of parental genomes creates genetic barriers, i.e., speciation (species’ self), as well as barriers to sequence mixing between related but polymorphic genes (individual self). Presumably, the unique immunological “self” provides for precision of immune surveillance against cellular “non-self” signals of infectious and non-infectious diseases.